Business Model from an Investor's Perspective: The Effectiveness of Experimental Approaches in Business Model Research - Masahiro KONDO (AAOS Transactions)
The purpose of this paper is to propose an approach to analyze a firm's business model from the investor's perspective. Until now, much research has been conducted on business models from the perspective of managers. In recent years, the term business model has been included in accounting systems and has become an important concept for investors. However, until now, business model research has not been conducted from the investor's perspective. This paper emphasizes the significance of discussing business model evaluation from the investor's perspective and identifies key concepts in business model research from the investor's perspective by integrating research in the fields of finance and management. Through a review of existing studies, the paper points out the importance of five axes in investors' business model evaluation: business model content, market content, number of business models, number of markets, and synergy effects. Furthermore, we finally propose a research approach using this framework and an experimental approach. We point out the possibility of new research by using the method of experimentation, which has rarely been used in business model research.